Mortgaging out and Related Problems - Ralph R. Neuhoff (Washington University Law Quarterly, 1961)
Under favorable conditions it is sometimes possible for a builder of property to mortgage it when completed for a sum measurably in excess of his cost, so that even before he sells the property or commences to operate it, he has, economically speaking, a profit in cash and in hand. It is the purpose of this Article to analyze the federal income tax law applicable to such situations. The interplay between the philosophy that increase of wealth should, in general, be subject to income taxation and the doctrine that there must be an outward event before an increase in economic wealth becomes taxable, has placed a burden upon the courts which they may not have handled too well. Furthermore, Congress has singled out several situations for special discriminatory treatment, probably in order to prevent a taxpayer from following through on the advantage gained by mortgaging out. Since the legislation applicable to these special situations is not necessarily called for by the logic of the situation, it is advisable for a taxpayer operating in this general area to be informed of it.
Keywords: Income tax -- United States; Mortgages